This I Believe - Murdock, Marcellus M. (Marcellus Marion) (Tufts Archival Research Center, 2006)
Marcellus Murdock remembers a near-death experience while flying that was a catalyst for transforming his beliefs from a materialist view of life to a spiritual one.